HUBUNGAN KEPEMIMPINAN DAN STRES KERJA TERHADAP KINERJA ANGGOTA POLISI - Fitrianto, Alif Bagus (2011)
This study aims to determine the relationship between leadership and job stress on the performance of police officers. The subjects in this study are all members of the police at Madiun district police some 700 members of the police and taken samples of some 236 members of the police. The sampling technique using cluster random sampling technique. Collecting data in this study using three (3) psychological scales is the leadership scale, the scale of job stress and performance scale. Data analysis technique using multiple regression statistical analysis techniques are two predictors. These relationships show that 1. The existence a positive between leadership and performance. rx 1 y = 0,229 with a significance level (p) = 0.000, (p <0.01). 2. The presence in a negative between job stress and performance. rx 2 y = -0,176 with a significance level (p) = 0.009, (p <0.01). 3. There is a strong enough relationship between leadership, work stress with variable performance. Leadership and work stress have an influence on the performance contribution of 8.0% with a value of R 2 = 0.080, F value = 10.178 count. The conclusion that can be drawn from this research that the relationship between leadership and job stress on the performance of members the police at police station Madiun is strong enough.